2015
DOI: 10.19030/jabr.v32i1.9536
|View full text |Cite
|
Sign up to set email alerts
|

Free Cash Flow And Earnings Management: The Moderating Role Of Governance And Ownership

Abstract: <p class="Default">The purpose of this paper is to analyze the moderating effect of corporate governance and ownership features in lessening earnings management practices in a free cash flow (FCF) situation. A simultaneous equations model is developed to address endogeneity of the FCF variable. Based on a sample of French companies belonging to the SBF 120 index from 2001 to 2010, the results highlight the opportunistic behavior of managers in presence of free cash flows. Particularly, managers engage in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 43 publications
4
17
1
2
Order By: Relevance
“…Owuigbe et al, (2019) found that independent commissioners and audit committees can minimize earnings management practices thereby reducing financial statement fraud. Nekhili et al, (2016) and Dowlatabadi & Filsaraei (2016) found a significant negative effect on good corporate governance and earnings management. Keshteli & Fathi (2015) did not find any influence on good corporate governance and earnings management.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Owuigbe et al, (2019) found that independent commissioners and audit committees can minimize earnings management practices thereby reducing financial statement fraud. Nekhili et al, (2016) and Dowlatabadi & Filsaraei (2016) found a significant negative effect on good corporate governance and earnings management. Keshteli & Fathi (2015) did not find any influence on good corporate governance and earnings management.…”
Section: Introductionmentioning
confidence: 94%
“…The existence of an audit committee in the company is expected to increase supervision of the company so as to create transparent company practices in order to minimize earnings management in the company (Abbadi et al, 2016). Nekhili et al, (2016) and Zarza, César, López, & Reguera (2018) showed a negative relationship between the audit committee and earnings management. This shows that the audit committee has succeeded in reducing the company's earnings management practices.…”
Section: The Effect Of Good Corporate Governance Mechanisms On Earninmentioning
confidence: 99%
See 1 more Smart Citation
“…Selanjutnya yang menjadi tujuan ketiga dari penelitian ini adalah untuk mengkaji hubungan antara free cash flow dengan earning management sekaligus untuk mencari bukti empiris terdapatnya pengaruh interaksi kedua variabel tersebut terhadap inefisiensi investasi perusahaan. Berdasarkan hasil-hasil penelitian terdahulu diperoleh bukti bahwa free cash flow memiliki korelasi yang signifikan dengan aksi earning management (Agustia, 2013;Kangarluei, Motavassel, dan Abdollahi, 2011;Karimi, Foladi, dan Shirazi, 2014;Kordlouie et al, 2012;Nekhili, Amar, Chtioui, dan Lakhal, 2016), namun arah korelasinya masih bertentangan antara hasil penelitian yang satu dengan hasil penelitian yang lainnya. Oleh karena itu, pertanyaan ketiga yang diajukan oleh penelitian ini adalah sebagai berikut: (Borad, 2019;La Rocca et al, 2007;Qingyuan, 2009;C.…”
Section: Pendahuluanunclassified
“…Earning management merupakan aksi intensional manajer untuk mencapai tujuan spesifik melalui prosedur akuntansi standar dalam bentuk memanipulasi laba sehingga nilai akrual berkurang atau bertambah (Chen, 2013 (Kangarluei et al, 2011;Nekhili et al, 2016).…”
Section: Pendahuluanunclassified